Time-lapse seismic signal analysis for enhanced oil recovery at Cranfield CO2 sequestration site, Cranfield field, Mississippi - Ditkof, J.; Caspari, E.; Pevzner, Roman; Urosevic, Milovan; Meckel, T.; Hovorka, S. (SOC EXPLORATION GEOPHYSICISTS, 2013)
The Cranfield field in southwest Mississippi has been under continuous Formula injection by Denbury Onshore LLC since 2008. Two 3D seismic surveys were collected in 2007 and 2010. An initial 4D seismic response was characterized after three years of injection, where more than three million tons of Formula remain in the subsurface. This interpretation showed coherent seismic amplitude anomalies in some areas that received large amounts of Formula but not in others. To understand these effects better, we performed Gassmann substitution modeling at two wells: the 31F-2 observation well and the 28-1 injection well. We aimed to predict a postinjection saturation curve and acoustic impedance (AI) change through the reservoir. Seismic volumes were cross-equalized, well ties to seismic were performed, and AI inversions were subsequently carried out. Inversion results showed that the change in AI is higher than Gassmann substitution predicted for the 28-1 injection well. The time-lapse AI difference predicted by the inversion is similar in magnitude to the difference inferred from a time delay along a marker horizon below the reservoir.